La influencia de la jurisprudencia internacional de los derechos humanos en la práctica judicial interna: el caso de la prisión preventiva - Donadio Linares, Luciano Martín (2023)
This article starts by describing the inte rnational judicial doctrine regarding the criteria for the imposition of an interim measure restricting freedom, such as preventive detention. It then analyzes the influence of these criteria in the internal judicial practice during the decision-making process, particularly in the context of a process of adaptation of internal law to international obligations, both universal and regional, meaning, in practice, the attr ibution of rationality to an extreme and exceptional measure, which can only be justified when it is necessary, proportionate and a concrete procedural danger has been proven.